Dual-pressure vaporization Kalina cycle for cascade reclaiming heat resource for power generation. (December 2015) - Guo, Zhanwei; Zhang, Zhi; Chen, Yaping; Wu, Jiafeng; Dong, Cong
Graphical abstract: Schematic of the dual-pressure evaporation Kalina cycle. Highlights: Dual-pressure vaporization Kalina cycle for high-grade heat resource is investigated. It is designed with 2nd evaporation branch for cascade utilization of heat resource. Work and basic concentrations, dew point temperature of evaporation are optimized. Power recovery efficiency of proposed cycle is 17% higher than that of Kalina cycle. Dual- p vaporization Kalina cycle fits reclaiming heat resource higher than 350 °C. Abstract: To further improve the cycle efficiency with the heat transfer curves between higher than 350 °C heat resource and the evaporating working medium of the Kalina cycle and to reduce the exhaust temperature of heat resource, the dual-pressure vaporization Kalina cycle for cascade utilization of high-to-mid grade heat resource is proposed. The optimization was conducted for parameters in this modified Kalina cycle such as concentrations of work solution and basic solution, evaporation dew point temperature. Under the conditions of inlet temperatures of heat resource and cooling water of respectively 400 °C and 25 °C and the constraints of proper heat transfer pinch point temperature differences, the maximum evaporation pressure not exceeds 20 MPa, the vapour quality at the turbine outlet is greater than 0.85 and the exhaust temperature of heat resource is not lower than 90 °C, the optimum parameters are obtained that the work and basic concentrations are 0.45 and 0.272 respectively, the dew point temperature of evaporation is 300 °C, and the corresponding power recovery efficiency of the dual-pressure vaporization Kalina cycle reaches 27%, which is 17% higher than that of the Kalina cycle with optimum parameters.